Respuesta :

Gravity due to any planet on its surface is given by

[tex]g = \frac{GM}{R^2}[/tex]

here we have

[tex]M = \rho*\frac{4}{3}\pi R^3[/tex]

[tex]g = \frac{G*\rho*\frac{4}{3}\pi R^3}{R^2}[/tex]

[tex]g = \frac{4}{3}*\rho*\pi*G*R[/tex]

Now since the gravity due to both planets are same

[tex]g_x = g_e[/tex]

[tex]\frac{4}{3}*\rho_e*\pi*G*R_e = \frac{4}{3}*\rho_x*\pi*G*R_x[/tex]

[tex]\rho_e*R_e = \rho_x*R_x[/tex]

now we have

[tex]\frac{r_x}{r_e} = \frac{\rho_e}{\rho_x}[/tex]

so above is the ratio of the radius